Data supporting: 'Electromagnetic Field Controlled Domain Wall Displacement for Induced Strain Tailoring in BaTiO3-Epoxy Nanocomposite' - Yazdani Nezhad, Hamed; Li, Danning; Barrington, James; James, Stephen W.; Ayre, David; Sloma, Marcin; Lin, Meng-Fang (Cranfield University, 2022)
This dataset is comprised of 4 files: 100W_strains, 100W_temperature, 440W_strains, and 440W_temperature.Failure in an epoxy polymer composite material is prone to initiate by the coalescence of microcracks in its polymer matrix. As such, matrix toughening via addition of a second phase as rigid or/and rubber nano/micro-particles is one of the most popular approaches to improve the fracture toughness across multiple scales in a polymer composite, which dissipates fracture energy via deformation mechanisms and microcracks arrest. Few studies have focused on tailorable and variable toughening, so-called ‘active toughening’, mainly suggesting thermally induced strains which offer slow and irreversible toughening due to polymer’s poor thermal conductivity. The research presented in the current article has developed an instantaneous, reversible active toughening composite based upon contact-less introduction of a microscopic compressive extrinsic strain field via remote electromagnetic radiation. Quantification of the extrinsic strain evolving in the composite with the microwave energy has been conducted using in-situ realtime fibre optic sensing. A theoretical constitutive equation correlating the exposure energy to micro-strains has been developed, with its solution validating the experimental data and describing their underlying physics. The research has utilised functionalised dielectric ferroelectric nanomaterials, barium titanate (BaTiO3), as a second phase dispersed in an epoxy matrix, able to introduce microscopic electro-strains to their surrounding rigid epoxy subjected to an external electric field (microwaves, herein), as result of their domain walls dipole displacements. Epoxy Araldite LY1564, a diglycidyl ether of bisphenol A (DGEBA) associated with the curing agent Aradur 3487 were embedded with the BaTiO3 nanoparticles. The silane coupling agent for the nanoparticles’ surface functionalisation was 3-glycidoxypropyl trimethoxysilane (3-GPS). Hydrogen peroxide (H2O2, 30%) and acetic acid (C2H4O2, 99.9%) used as functionalisation aids, and the ethanol (C2H6O, 99.9%) used for BaTiO3 dispersion. Firstly, the crystal microstructure of the functionalised nanoparticles and the thermal and dielectric properties of the achieved epoxy composite materials have been characterised. It has been observed that the addition of the dielectric nanoparticles has a slight impact on the curing extent of the epoxy. Secondly, the surface-bonded fibre bragg grating (FBG) sensors have been employed to investigate the real-time variation of strain and temperature in the epoxy composites exposed to microwaves at 2.45 GHz and at different exposure energy. The strains developed due to the in-situ exposure at composite, adhesive and their holding fixture material were evaluated using the FBG. The domain wall induced extrinsic strains were distinguished from the thermally induced strains, and found that the increasing exposure energy has an instantaneously increasing effect on the development of compressive strains. Post-exposure Raman spectra showed no residual field in the composite indicating no remnant strain field examined under microwave powers
Keywords: 'Dielectric nanocomposites'; 'active toughening'; 'Ferroelectrics'; 'Barium titanate'; 'Domain wall movement'; 'Extrinsic strain'; 'Microwave radiation'